Progress in Arrhythmia - Rivera-Caravaca, José Miguel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on novel and scarcely investigated topics in relation to atrial fibrillation (AF), from the role of f-wave harmonic spectral structures in improving the preoperative prediction of catheter ablation outcomes in AF to the design of a study to investigate the effectiveness of a hand-held device in screening for AF when embedded into the handles of supermarket trolleys. However, the management of AF is so complex that this Special Issue also explores the therapeutic approach to AF in patients with congenital hemophilia, provides exercise recommendations for patients with AF, and includes broader investigations, such as on the impact of integrated care on oral anticoagulation quality, the identification of clinical phenotypes to stratify mortality risk, and the assessment of differences in biomarkers between AF patients and healthy controls.